The long run stability of money demand in the proposed West African Monetary Union - Simplice Asongu; Oludele E. Folarin; Nicholas Biekpe (African Governance and Development Institute (AGDI), 2018)
This study examines the stability of money demand in the proposed West African Monetary Union (WAMU). The study uses annual data for the period 1981 to 2015 from thirteen of the fifteen countries making-up the Economic Community of West African States (ECOWAS). A standard money demand function is designed and estimated using a bounds testing approach to co-integration and error-correction modeling. The findings show divergence across ECOWAS member states in the stability of money demand. This divergence is informed by differences in cointegration, stability, short run and long term determinants, and error correction in event of a shock.
Keywords: E41; C22; 330; Stable; demand for money; bounds test